Investing in Professional Judgment-in-Action: Negotiating Relationships That Enhance Trust, Responsibility, and Efficacy - Cynthia J. Reed; Margaret Ross (Educational Considerations, 2001)
Teachers’ judgment-in-action has been maligned by current policies and legislation, as well as the cultures and structures of schools. During the last decade, there have been numerous calls for educational reform, often accompanied by expanded legislation to control, structure, and evaluate schools.